Effects of interrupting daily sedentary behavior on children's glucose metabolism: A 6‐day randomized controlled trial. Issue 8 (14th October 2022) - Broadney, Miranda M.; Belcher, Britni R.; Ghane, Nejla; Sheni, Risha; Jayson, Michael J.; Trenschel, Robert W.; Collins, Shavonne M.; Brychta, Robert J.; Davis, Elisabeth K.; Brady, Sheila M.; Yang, Shanna B.; Courville, Amber B.; et al.
Abstract: Background: Metabolic disease risk in youth is influenced by sedentary behaviors. Acute in‐lab studies show that, during a single day, interrupting a sedentary period with short bouts of physical activity improves glucometabolic outcomes. Objective: To determine if acutely improved glucose metabolism persists after multi‐day interruptions of sitting with walking brief bouts. We hypothesized that children who underwent interrupting sitting on multiple days would demonstrate lower insulin area under the curve during an oral glucose tolerance test compared to uninterrupted sitting. Methods: Healthy, normoglycemic children ( N  = 109) ages 7–11 years were randomized to one of two conditions: Control (3 h of daily Uninterrupted Sitting) or Interrupted Sitting (3‐min of moderate‐intensity walking every 30 min for 3 h daily); with dietary intake controlled through provision of foodstuffs for the entire experiment. Participants attended six consecutive daily visits at a research ambulatory unit. The primary outcome was insulin area under the curve during the oral glucose tolerance test on day 6 during interrupted or uninterrupted sitting; secondary outcomes included glucose and c‐peptide area under the curve, energy intake at a buffet meal on day 6, and free‐living activity. Results: Among 93 children (42 uninterrupted sitting, 51 interrupted sitting), daily interrupted sitting resulted in 21% lower insulin ( β  = 0.102 CI:0.032–0.172, p  = 0.005) and a 10% lower C‐peptide ( β  = 0.043, CI:0.001–0.084, p  = 0.045) area under the curve. Matsuda and Glucose Effectiveness Indices were also improved ( p 's < 0.05). There were no group differences in energy intake or expenditure. Conclusions: Sustained behavioral change by interrupting sedentary behaviors is a promising intervention strategy for improving metabolic risk in children.